Alterações fisiológicas e metabólicas associadas com a tolerância à salinidade em sorgo - Oliveira, Daniel Farias de (2020)
Salinity is an abiotic stress that strongly limits plant growth, development and productivity, especially in arid and semiarid regions. Survival in saline environments depends on several adaptive processes, which involve absorption, transport and distribution of ions in various plant organs, accumulation of organic solutes in cells and an efficient antioxidant defense system to combat oxidative stress. Using two sorghum genotypes with different degrees of tolerance to salt stress, CSF20 (tolerant genotype) and CSF18 (sensitive genotype), were analyzed the effects of salinity (NaCl 75 mM) on growth, ion contents (Na+, K+ and Cl–), gas exchange and chlorophyll a fluorescence, levels of photosynthetic pigments (chlorophylls a and b, carotenoids), relative water content (TRA) and osmotic potential (Ψo). In addition, were also analyzed the effects on the accumulation of compatible solutes (γ-aminobutyric acid, proline, free amino acids and soluble sugars), levels of polyamines (putrescine, spermidine and spermine) and enzyme activities of the polyamines metabolism. Were also quantified the contents of O2– and H2O2, integrity of biological membranes, enzymes activities of the antioxidant system and the metabolic profile (metabolome) for both genotypes. Salinity promoted reductions in growth and induced increases in Na+ and Cl– contents and decreased K+ content. Salt stress affected gas exchange, chlorophyll a fluorescence emission parameters and carotenoid contents, except for stomatal conductance, internal CO2 concentration, transpiration, ETR and chlorophyll content. TRA and Ψo were reduced by salt stress, but to reduce damage, especially in CSF20, osmotic adjustment was performed with accumulation of osmolytes and polyamines. Salinity induced increases in the levels of putrescine, in the sensitive genotype, and spermidine and spermine, in the tolerant genotype, and this was probably due to the regulation of the activity of the oxidative enzymes of polyamines, diamine oxidase and polyamine oxidase. The contents of O2– and H2O2 in the CSF18 genotype increased due to salinity, while in the CSF20 genotype an increase was observed only in the content of H2O2. Membrane integrity was compromised by salinity in both genotypes, but this effect was less pronounced in CSF20. Oxidative damage to the leaves of sorghum plants was more pronounced in the CSF18 genotype. In general, the activities of superoxide dismutase, catalase, ascorbate peroxidase and glutathione reductase enzymes in sorghum leaves were altered by salinity. Oxidative damage was observed in greater intensity in the salinity-sensitive genotype, which showed lower activity of antioxidative enzymes and high levels of reactive oxygen species. The metabolome analysis showed that salinity increases the biosynthesis of polyamines (spermidine and cadaverine), with accumulation of important compatible solutes, such as sugars, polyols and proline, in addition to tricarboxylic acid cycle intermediates in the CSF20 genotype, but not in the sensitive genotype. Both genotypes studied were affected by salt stress, but differences in growth confirmed that CSF20 is more tolerant to salt stress than CSF18. The results, therefore, suggest a greater plasticity of the genotype tolerant to changes in environmental conditions, with alterations in metabolism that favor growth under adverse conditions.